New understanding about the relationship among neurocysticercosis, seizures, and epilepsy. (August 2021) - Carpio, Arturo; Romo, Matthew L.; Hauser, W. Allen; Kelvin, Elizabeth A.
Highlights: In neurocysticercosis (NC), acute symptomatic seizures are caused by parasite degeneration and most do not evolve to epilepsy. Patients with NC are at higher risk for epilepsy than the general population, although cross-sectional studies may overstate this association. Calcification is an epileptogenic substrate associated with seizure recurrence. In randomized trials, seizure recurrence after cyst resolution was similar in those receiving antiparasitic treatment compared with placebo. Seizures and epilepsy due to NC generally have a good prognosis. Abstract: Epilepsy and neurocysticercosis are common neurological disorders and are major public health issues that contribute to the world's burden of disease. Acute symptomatic seizures, the main clinical manifestation of parenchymal neurocysticercosis, are caused by the host brain immune-inflammatory process in response to the death or degenerative phase of the parasite. Seizures may recur over the course of several months while the local inflammatory activity lasts. If the seizures recur once the acute process resolves, the patient can be diagnosed as having epilepsy. However, most acute symptomatic seizures secondary to neurocysticercosis do not evolve to epilepsy. Recent prospective studies suggest that the development of epilepsy, while more common than in the general population, is not as common in neurocysticercosis patients as originally suggested by cross-sectional studies. Antiparasitic treatment has been found to hasten the transition of cysts from the active phase to the degenerative phase and is associated with a short-term reduction in focal seizures after treatment. However, antiparasitic treatment has not been found to affect the transition from the degenerative phase to calcification, which is an epileptogenic substrate associated with subsequent epilepsy. In this narrative review, we critically appraise the relationship among neurocysticercosis, seizures, and epilepsy in the context of new developments in the literature.